HISTORY OF THE DEVELOPMENT OF AEROPLANES IN THE INDIAN SUBCONTINENT IN PRE-INDEPENDENCE PERIOD - Ray, Moitreya (International Journal of Research -GRANTHAALAYAH, 2022)
Winning the blue sky became possible with the invention of the motor operated aero plane by Orville Wright and Wilbur Wright—the Wright Brothers in 1903. Shortly after their invention, aeronautic companies established in America and Europe started manufacturing aero planes. The year 1911 marked the beginning of the Civil Aviation in India when the Humber-Sommer biplane manufactured in England by Humber took 10-kilometre (approx.) flight in 15 minutes carrying about 6,500 mails. Since then, a continuous technological advancement in aero plane manufacturing had been noticed that not only contributed significantly to the military aviation during the two World Wars but also flourished the Civil Aviation sector for fastest communication worldwide. Prior to the Independence of India, a good number of aero plane models manufactured by different companies occupied the Aviation Sector. It is a matter of proud that India was among the privileged countries where aviation started within a decade of its invention. More than a century old Indian Civil Aviation at present is one of the fastest developing aviation markets in the world according to the International Air Transport Association (IATA). In this present paper an attempt has been taken to document the various aero planes flew in the sky of the Indian Subcontinent to understand the history of the Indian Civil Aviation in the pre-Independence period in the light of its demand and popularity that led India in achieving scientific temperament and technological advancement.